Penalties and optimality in financial contracts: Taking stock - Michel A. Robe; Eva-Maria Steiger; Pierre-Armand Michel (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2006)
A popular view of limited liability in financial contracting is that it is the result of societal preferences agnainst excessive penalties. the view of most financial economists is instead that limited liability emerged as an optimal institution when, in the absence of a clear limit on economic agents liability, the development of some economic activities might have been thwarted, Viewing the institution from the perspective of optimal legal system design allows us to better understand the current debate on it. We present a broad history of penalties in financial contracts to highlight the interactions between technology, legal environments, purpose of the financial relationship, and contractual provisions. We show that harsh monetary and non-pecuniary penalties are not mere relics from a bygone era and, at the same time, that limited liability is far from a recent institution. We then discuss trade-offs associated with legal mandates of either unlimited or limited liability, both for the contractin parties and for the rest of Society. We identify two broad patterns. First, the toughness of liability rules and bankruptcy laws decreases as exogenous sources of uncertainty become relatively more important, and increases with the opportunity for moral hazard (related to diligence, risk taking, or deception).Second, bankruptcy laws become more lenient as the scope for labor specialization and the returns to human capital or entrepreneuship increase.
Keywords: G32; D82; 330; Limited Liability; Bankruptcy; Debt Bondage; Debtor's Prison; History